Use of Chitosan Adhesive for the Manufacture of Corrugated Fibreboard - Srinivasa Gopal, T.K.; Thankamma, R.; Ramachandran Nair, K.G.; Prabhu, P.V.; Madhavan, P. (Fishery Technology, 2025)
Peeling strength of kraft paper-kraft paper and kraft paper- corrugated fibreboard (CFB) bonded using 1.5% chitosan in 1% acetic acid of viscosities 20, 130 and 500 cp and starch were compared. The peeling strength between kraft paper-kraft paper and kraft paper- corrugated fibreboard was same in both starch and chitosan (1.5% and 130 cp viscosity) adhesive. The frozen storage behaviours of 5 ply corrugated fibre board prepared using 1.5% chitosan of viscosity 130 cp and starch solution having 10% solids were studied. The bursting strength, puncture resistance and flat crush strength were reduced during storage, but the amount of reduction was more in CFB using starch based adhesive. The starch based adhesive board delaminated on immersion in water while chitosan based adhesive board did not delaminate. CFB using chotosan adhesive had more compression strength than the starch adhesive CFB.